From “woman in jeopardy” to COVID-19 lockdown: the gender gap in TV movies aired on Spanish generalist television (2005-2020) - Tello Díaz, Lucía (Routledge, 2022)
The number of TV movies aired on Spain television over the last decade has increased exponentially. These primarily North American and German productions not only take up a large part of lunchtime and the afternoon; they also portray women rooted in gender stereotypes that are clearly at odds with the female gender values of autonomy and equal rights. However, 2017 saw an increase in female directors making TV movies portraying women in a significant variety of roles. This trend, which continues during the COVID‑19 pandemic, has led to a partial shift in the construction of gender. Our research assesses the transformation of gender portrayal and the ideological construction behind TV movies, including their subject matter, lead characters, frequency of airings, and target audience. This study also examines women’s roles in TV-movie production, including screenwriting and directing, and seeks to ascertain the leading TV-movie production companies that broadcast their output in Spain and address the business philosophy behind these producers. Finally, we review the Spanish channels that most frequently schedule TV Movies in large numbers, as well as their guidelines, target and vision. © 2021 Informa UK Limited, trading as Taylor & Francis Group.
Publicación con el texto completo en acceso restringido
Keywords: COVID-19; gender; Spain; stereotypes; TV movies; women; Scopus; JCR